(untitled) (Research, Society and Development, 2022)
Bloodstream infections represent a challenge for public health, are extremely frequent in a hospital environment and are related to high rates of morbidity and mortality and increased hospital costs, especially in critical sectors such as Intensive Care Units, with early diagnosis being fundamental. This study aims to collect and analyze data on bacterial incidence and susceptibility profile of microorganisms isolated in blood cultures of patients hospitalized in the Intensive Care Unit of Fundação Hospitalar São Lucas de Cascavel/PR. This is a cross-sectional, retrospective study, with a quantitative approach and of a descriptive nature, using data of interest from medical records and laboratory test results, in the period between July 2019 and July 2021. 210 positive blood cultures were analyzed , the most affected were male (69.52%) and people aged over 60 years (45.71%). Among the gram-positive microorganisms, the most common were coagulase-negative Staphylococcus (44.70%), Staphylococcus aureus (10.47%) and Enterococcus faecalis (2.38%). Among the gram-negatives, the most frequent were Klebsiella spp. (12.85%), Pseudomonas aeruginosa (9.52%), Enterobacter cloacae (4.76%). Regarding mortality, a percentage of 49.43% was observed among gram-positives and 44.62% among gram-negatives. An important diagnostic resource for the detection of microbial pathogens is blood culture, enabling knowledge of the bacterial profile found in hospitalized patients, which allows for a targeted and effective treatment and, consequently, helps to reduce the selection of multidrug-resistant bacteria, helping in the prevention and control of hospital infections.